Dipolar Nanocars Based on a Porphyrin Backbone. Issue 52 (25th August 2020) - Nishino, Toshio; Martin, Colin J.; Takeuchi, Hiroki; Lim, Florence; Yasuhara, Kazuma; Gisbert, Yohan; Abid, Seifallah; Saffon‐Merceron, Nathalie; Kammerer, Claire; Rapenne, Gwénaël
Abstract: The design and synthesis of a new family of nanocars is reported. To control their motion, we integrated a dipole which can be tuned thanks to strategic donor and acceptor substituents at the 5‐ and 15‐positions of the porphyrin backbone. The two other meso positions are substituted with ethynyltriptycene moieties which are known to act as wheels. Full characterization of nine nanocars is presented as well as the electrochemistry of these push‐pull molecules. DFT calculations allowed us to evaluate the magnitude of the dipoles and to understand the electrochemical behavior and how it is affected by the electron donating and accepting groups present. An X‐ray crystal structure of one nanocar has also been obtained. Abstract : A new family of nanocars is reported. To control their motion, a dipole has been integrated which can be tuned thanks to donor and acceptor substituents present at the 5‐ and 15‐positions of the porphyrin backbone. The two other meso positions are substituted with ethynyltriptycene moieties which are known to act as wheels.